Characterization of Ficus carica L. cultivars by DNA and secondary metabolites analysis: Is genetic diversity reflected in the chemical composition? - Oliveira, Andreia P. (2014)
Ficus carica L. is one of the first plants cultivated by humans, having a great economic impact in many countries, the fruit being an important constituent of the Mediterranean diet. Plants' metabolome may be influenced by their genetic diversity, environmental factors and their interaction. Thus, in this study we explored the chemical and morphological profiles and the DNA of five Portuguese F. carica cultivars, to try to establish a correlation between genetics and metabolome. Morphological and molecular markers of these cultivars were assessed for the first time. Besides the observed morphological differences, the rbcL chloroplastic DNA region allowed a better clustering of the cultivars and was more successful in the identification of the species; as so, it could be helpful for authenticity purposes. Phenolic compounds, sterols and triterpenes profiles were determined by HPLC/DAD, the last revealing to be less variable among cultivars, once only a significant difference in the betulol content of “Pingo de Mel” samples was observed. For almost all the accessions studied, no correlation between genetic diversity and composition was observed.